SENSORY ANALYSIS OF SAUSAGE ‘FRESCAL’ MADE OF LAMB MEAT AND DRIED FRUITS - Igor Shoiti Shiraishi (Revista Tecnológica, 2022)
The food market is in constant reinvention and understanding the needs of your target audience and the trends of agribusiness is as important as knowing how to harmonize ingredients and flavors. The ‘frescal’ sausage for barbecue is one of the most appreciated meats in Brazil and its combination with dried fruits can add flavor to the final product. Thus, the present work aimed to evaluate the acceptance of a differentiated product based on ‘frescal’ lamb meat and dried fruits with a total of four formulations. The products were tested by an untrained panel, totaling 150 participants for each of the formulations. The results showed better acceptance by two products, both containing dried figs, but in different concentrations. For both analyzed formulations, the preference is indicated for males, who presented higher scores for most of the evaluated items. Age group analysis showed better acceptance within the range of 31 to 35 years. The majority of the sensory panel would buy the products monthly (45.20 and 53.80%, respectively), being the barbecue occasion the most suitable. Once the profile of potential consumers was delimited, the insertion in the market represents potential benefits for aggregation of value for meat processing and for the small sheep producers.